(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
Several tens of Lower Bathonian Bigotites from Digne-Castellane region (SE France) and Cabo Mondego area (Portugal) have been reviewed. Three species have been distinguished in the lowermost subzone of the Zigzag Zone (Parvum Subzone) just above the boundary Bajocian to Bathonian: B. diniensis Sturani [M+m], B. sturanii sp. nov. [M+m] and B. mondegoensis sp. nov. [M+m]. In the Bas Auran area, a chronocline from evolute, strongly ribbed and constricted forms (including B. sturanii and B. diniensis) to involute forms with blunt, moderately prominent ribbing and weak constrictions (including B. mondegoensis) can be recognized. The shared taxa B. mondegoensis sp. nov. and possibly B. diniensis Sturani permit detailed subdivision and correlation to be established between ammonite fossil assemblages of Parvum Subzone in the Lusitanian and Alpine basins. A separate genus of Zigzagiceratinae, Protozigzagiceras g. nov., is proposed to encompass P. torrensi (Sturani) as type species. These new palaeontological data about the youngest members of Bigotitinae and the oldest members of Zigzagiceratinae are of biochronostratigraphic importance for the subdivision and correlation of the basal Bathonian Zigzag Zone. Three successive biohorizons can be identified at the Parvum Subzone in Bas Auran (French Alpine Basin) and Cabo Mondego (Lusitanian Basin): Diniensis, Mondegoensis and Protozigzagiceras biohorizons.